Diverting tyrosine: Data from untargeted metabolic analysis of tomato fruit accumulating L-DOPA - Dario Breitel; Paul Brett; Saleh Alseekh; Alisdair R. Fernie; Eugenio Butelli; Cathie Martin (Data in Brief, 2021)
L-DOPA, also known as Levodopa or L-3,4-dihydroxyphenylalanine, is synthesised in plants from the amino acid tyrosine, through oxidation. Conversion of tyrosine to L-DOPA constitues the first step of betalain biosynthesis in plants. Recently, the gene responsible for this step was identified in beetroot, BvCYP76AD6, that is the source of yellow and purple betalain pigments. Overexpression of this gene, specifically in tomato fruit, led to accumulation of L-DOPA that otherwise is not detectable [1]. Co-expression of the Arabidopsis transcription factor, AtMYB12, in fruit, increased L-DOPA levels further. To study the metabolic changes in these fruit, we performed untargeted metabolite analysis of ripe fruit: GC-MS was performed to identify changes in primary metabolites, LC-MS analysis was used to identify alterations in specialised metabolites. These data can be used to study the impact of diversion of tyrosine in fruit, accompanied by the accumulation of L-DOPA in planta and to identify new biological roles associated with the accumulation of these metabolites.